2019
DOI: 10.48550/arxiv.1911.07799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hecke insertion and maximal increasing and decreasing sequences in fillings of stack polyominoes

Abstract: We prove that the number of 01-fillings of a given stack polyomino (a polyomino with justified rows whose lengths form a unimodal sequence) with at most one 1 per column which do not contain a fixed-size northeast chain and a fixed-size southeast chain, depends only on the set of row lengths of the polyomino. The proof is via a bijection between fillings of stack polyominoes which differ only in the position of one row and uses the Hecke insertion algorithm by Buch, Kresch, Shimozono, Tamvakis, and Yong and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Backelin, West and Xin [1] have shown that the number of transversal fillings of a Ferrers shape that avoid δ k is the same as the number of such fillings that avoid ι k . This was later generalized to non-transversal fillings [13], and to more general shapes, such as stack polyominoes [8], moon polyominoes [15], or almost-moon polyominoes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Backelin, West and Xin [1] have shown that the number of transversal fillings of a Ferrers shape that avoid δ k is the same as the number of such fillings that avoid ι k . This was later generalized to non-transversal fillings [13], and to more general shapes, such as stack polyominoes [8], moon polyominoes [15], or almost-moon polyominoes [14].…”
Section: Introductionmentioning
confidence: 99%